Species Diversity and Herbal Medicine Utilization of Mangrove Plants: A Comparative Study among Coastal Communities in Lampung - Duryat; Yuwono, Slamet Budi; Riniarti, Melya; Hidayat, Kuswanta Futas; Hidayat, Wahyu; Rodiani; Damai, Abdulah Aman; Prasetyo, Pangestu; Dani, Hafiz Ansori (Jurnal Sylva Lestari, 2024)
Biodiversity and local wisdom in mangrove ethnopharmacology are essential to study as a basis for conservation and health development. The study objectives were determining mangroves’ diversity and distribution, their use as herbal medicine, and their trusted medical properties. Vegetation analysis was employed to study the mangrove diversity. An interview and observation were conducted to study mangrove utilization. Mangrove diversity was determined by examining the diversity index. Mangrove utilization was determined by descriptive comparative analysis and calculating species use value, plant part value, and fidelity level. Total 28 species of mangroves from 15 families in Lampung. The highest mangrove diversity is in Lampung Timur (22 species; Shannon Index (H') = 1.93), followed by Pesawaran (21 species; H' = 1.96), Tulang Bawang (12 species; H' = 1.24), and Lampung Selatan (11 species H' = 0.90). Surprisingly, a species was used for different purposes in different areas. S. caeseolaris has the highest species use value of 0.1591. Leaves have the highest plant part value of 58%. R. apiculata, as an antiseptic, and S. caseolaris, as an antioxidant, have the highest fidelity level, 14%. Eight mangrove species trusted by the community have ten medical properties. This finding could be the basis for scientific studies to find new sources of medicine. Keywords: biodiversity, costal area, ethnopharmacology, herbal medicine, mangrove